Scenarios of Land-Use Change in Protected Forest of Wosi Rendani Manokwari District, West Papua, Indonesia - Mahmud Mahmud; Wahyudi Wahyudi; Heru Joko Budirianto; Bambang Nugroho (Jurnal Manajemen Hutan Tropika, 2017)
Protected forests have drawn international attention.  This research aims to determine scenarios of land-use change in Protected Forest of Wosi Rendani (PFWR).  The study was conducted using land evaluation approach to land unit, determination and alternative land use change, based on the potential and the level of threat for PFWR.  The results showed that PFWR should remain as a protected forest although the total score of forest modeling was 130. This forest serves to protect soil, water, and danger from floods and landslides. This region has springs, caves, and waterfalls, which can be further developed into eco-tourism and environmental services. As a city forest, PFWR makes Manokwari's weather cooler, enhances the quality of air, reduces environmental pollution, and adds catchment areas. As a community forest, PFWR has forest plants, agricultural crops and fruits, in which people are only allowed to take flowers, fruits, and seeds they have planted. As a buffer zone, PFWR serves as a buffer to reduce population pressures on the forest area or village surrounding the area with high interaction by integrating conservation and economic interests of the surrounding community. As cultivation and settlement, PFWR has three settlements, namely Soribo, Kentestar, and Ipingoisi, 4 settlements outside PFWR namely Tanah Merah Indah, Ajoi, Buton, Mako Brimob, as well as plots of land owned by developers such as Bank Arfindo, Lumintu, Irman Jaya, and Suntari. The final scenario of the land use change in PFWR depends on the policy of local and central government.